Fate of Sir John Franklin : the voyage of the 'Fox' in the Arctic seas in search of Franklin and his companions - M'Clintock, Francis Leopold, Sir, 1819-1907. (London : John Murray, 1881)
Author commanded the "Fox." "Reports on scientific observations obtained during the voyage of the 'Fox'; or references to such of these reports as are published elsewhere": p.321-327. Includes index. Issued also under titles: In the Arctic seas and The voyage of the 'Fox' in the Arctic seas. Mode of access: Internet. 2